Metal fluxes at the sediment-water interface in rivers in the Turvo/Grande drainage basin, So Paulo State, Brazil - Campanha, Mariele B. [UNESP]; Moreira, Altair Benedito [UNESP]; Bisinoti, Marcia Cristina [UNESP] (Springer Heidelberg, 2012)
Purpose The Turvo/Grande drainage basin (TGDB), located in the northwestern region of So Paulo state, covers an area of 15,983 km(2). The region is typically regarded as agricultural by the So Paulo State Environmental Agency, but the industrial area is expanding, and some studies have shown that metal concentrations in water can be higher than the values regulated by Brazilian law. Therefore, the aim of this study was to assess the role of sediments as a source or a sink of metals for drainage basin management.Materials and methods Interstitial water from different sediment depths (0-42 cm) and the sediment-water interface and sediment core samples were collected in February and July 2010 from the Preto, Turvo, and Grande rivers. Quantification of Cr, Cu, Fe, Mn, Ni, and Pb in these samples was performed by graphite furnace or flame atomic absorption spectrometry. Metal diffusive flux estimation from sediment into the overlying water was calculated by Fick's First Law of Diffusion.Results and discussion The fluxes of all metals for the three rivers were positive, indicating diffusion into the overlying water. Ni and Pb showed the lowest diffusive fluxes, which ranged from 2.4 to 3,978 mu g m(-2) day(-1) for Ni and from -0.1 to 1,597 mu g m(-2) day(-1) for Pb. In turn, Cu and Cr were subject to the largest transfer to water, especially in the dry season (Cr, 4.5-7,673 mu g m(-2) day(-1); Cu, 1.3-14,145 mu g m(-2) day(-1)). The Preto River (urban area) showed smaller fluxes than the Grande River (agricultural area), and the values of the latter were higher than those found in other impacted areas of the world.Conclusions The diffusive fluxes indicate that sediments from the TGDB act as a source of metals for the water column, with increased export of metals, particularly Cr and Ni, from the sediment into the overlying water during the dry season.
Keywords: Brazil; Diffusive fluxes; Geochemistry; Metals; Sediment porewaters; Turvo/Grande drainage basin